Homoeopathic Medicines and Breath vs Blood Alcohol Analysis (Advancements in Homeopathic Research, 2022)
Drinking and driving is an offence. Every country has set its own norms for permissible level of alcohol in the blood for safe driving. Homeopathic Medicines are Hydro Alcoholic, alcohol percentage varies from 40 – 90 percent. Purpose of this study is whether consumption of different forms of homoeopathic medicines alter the breath and blood alcohol levels and whether it exceeds the permissible safe limit for driving. This study was conducted at C. M. P. Homoeopathic Medical College in May -July2018 on 30 individuals with different forms of Homoeopathic medicines. Breath and Blood alcohol levels after homoeopathic medicines were estimated. After mother tincture and freshly prepared globules Breath alcohol levels are found higher than permissible level for short time of 1-5 minutes, but blood alcohol levels were not elevated.  20 drops of mother tincture and medicated globules can’t cause drunk driving.
Keywords: Homoeopathic medicines; breath alcohol; blood alcohol; breath analyzer